Strategic planning : - Jacob, M. E. L (Neal-Schuman Publishers, 1990)
Planning is an essential management skill, particularly as librarians increasingly need to justify their requests for--and use of-- resources. Here, the process is made simple through checklists, work forms, and examples that can be used by librarians to create an individualized planning workbook. Chapters explain the variables that contribute to successful planning, including underlying assumptions, environmental considerations, strategic focus, and both personal and institutional values and priorities. Advice on plan communication and format, maintenance, and updating is also provided.